Perfumed nightmare - Kidlat Tahimik; Eric de Guia; Flower Films ([Manila] Flower Films, 1976)
A young Filipino (Kidlat) who earns his living by driving a jeepney is obsessed by a dream of visiting America and Cape Canaveral. One day an American offers him a work in France. In Paris, his only friend is lola, a street vendor of eggs who fears she cannot survive the market flooded with cheap synthetic eggs. Soon, Kidlat's dream become a perfumed nightmare, full of supermarkets and supertechnologies but no paradise.
DVD
Kidlat Tahimik, Dolores Santamaria. Georgette Baudry, Katrin Muller, Hartmut Lerch.
Keywords: Feature films